Islamic banking: an exploratory study of public perception in Uganda - Lujja, Sulaiman; Mohammed, Mustafa Omar; Hassan, Rusni (Emerald, 2018)
Purpose – Islamic banking (IB) has been globally embraced by over 76 countries, with over $2tn in assets. Despite this remarkable progress, there are countries that are yet to fully embrace IB (Uganda inclusive). All the ongoing initiatives in Uganda (at policy level) to establish IB require supporting study of public awareness and attitudes toward IB. This will stimulate a down-top approach to the feasibility of IB and policymaking, thus providing a fertile ground for wider consideration of the majority stakeholders’ views in formulating standards and policy guidelines regulating IB. This study aims to explore the perception of Ugandans towards IB. Design/methodology/approach – The study is exploratory in nature and uses a quantitative method. Out of the 400 questionnaires distributed, only 354 were usable for further analysis. SPSS 21 was used to analyze data using descriptive statistics and factor analysis. Findings – Major findings indicate that unlike non-Muslims, Muslims are more knowledgeable about the IB culture, although both groups have low awareness about IB terminologies. There were inconsistences in Muslim and non-Muslim attitudes toward IB, for instance; while non-Muslims are motivated by “profitability”, Muslims’ inclination to IB is mainly due to “religious and profitability combined”. Both groups demonstrated some uniformity in their selection criteria of banks such as “third party influence”, although they are inconsistent in other factors. Originality/value – The novelty of this study rests in its down-top approach to feasibility of IB by gauging the perception of majority stakeholders before IB is established. The study is conducted in a heterogeneous society unlike many of similar studies that have focused on Muslim majority countries. As most studies (with similar background) are at least 18 years old, this study remains outstanding in gauging the dynamics of stakeholders in Muslim minority countries which have yet established IB.